Fall of Hades - Evans, Richard Paul (Evans, Richard Paul. Michael Vey, 2017)
Michael and the Electroclan embark on their deadliest mission yet, stealing the Elgen boat holding all their money. If the Electroclan can rescue three Elgen youth condemned to death and join a Guard member who's looking to rebel, they might just stand a chance at success.